The value of a human life in ancient Egyptian religion at the turn of the 3rd –2nd millennia BC - A. E. Demidchik (Шаги, 2024)
The author explores the ancient Egyptian religion’s perspective on value of a human life during the latter part of the Old Kingdom, the First Intermediate Period, and the Middle Kingdom. Polytheistic ritualistic “communal” religions, where ethics did not play a significant role, are typical for the epoch of early antiquity, and the Egyptian views discussed in the article mostly align with this context. It was believed that the gods were concerned about the Egyptian people’s safety and well-being primarily because these were indispensable preconditions for abundant provisions and seamless performance of divine cults. Created ultimately to produce and offer sacrificial gifts to the gods, the Egyptians were kind of their “flock”, “the gods’ (little) livestock”. However, the gods were thought to have little involvement in the individual lives of the king’s subjects: their benevolent attention was focused on the pharaoh, who personified the state. Since the king formally was the sole authorized performer of liturgical rituals, Egyptian religion had a pronounced communal nature that hindered the development of the concept of a man’s enduring personal connection with a deity. Within this framework, moral excellence was deemed essential for an individual to gain favor with the ruler, whereas divine recompence during one’s lifetime for piety and virtue was deemed hardly predictable.